Operational Efficiency Analysis and Ebitda Improvement Strategies: A Case Study of Indonesian Construction Chemicals Distribution - Faldy Ilman (International Journal of Science and Environment (IJSE), 2025)
This study investigates the operational efficiency paradox in a mid-sized Indonesian construction chemicals distributor experiencing significant revenue growth (73.4% from 2022-2024) alongside declining EBITDA margins (from 7.07% to 6.50%). Using Activity-Based Costing, Value Stream Mapping, Porter's Value Chain Analysis, and industry benchmarking, the research identified seven critical operational inefficiencies costing IDR 1.36-1.79 billion annually (37-48% of operating income). Key inefficiencies include inventory management deterioration (turnover declining from 13.21x to 9.60x), warehouse productivity deficits (20-36% below industry benchmarks), and technology underutilization. The study developed a comprehensive three-phase improvement roadmap requiring IDR 1.54 billion investment to generate IDR 2.32 billion in recurring annual savings, projecting operating margin improvement from 6.50% to 10.56%. Phase 1 quick wins (IDR 165M investment) deliver 311% ROI within 3 months, demonstrating self-funding viability. Benchmarking against industry standards validates improvement targets as conservative and achievable. The research contributes to operations management literature by demonstrating integrated framework application in emerging markets and provides practical guidance for mid-sized B2B distributors facing similar profitability challenges.